Forecasting of Health Sector Stock Prices During Covid-19 Pandemic Using Arima And Winter Methods - Tamamudin, Tamamudin; Rusyida, Wilda Yulia (Sinkron : jurnal dan penelitian teknik informatika, 2022)
This study aims to compare the accuracy of the ARIMA and WINTER methods in forecasting or predicting the daily stock price of the health sector. The data used in this study is secondary data in the form of historical data on the daily share price of PT. Darya Varia Laboratori, PT. Indofara Persero, PT. Kimia Farma, PT. Kalbe Farma, and PT. Merck Indonesia from March 14, 2020 to April 14, 2021. From the results of the research, PT. Kimia Farma is suitable to use the ARIMA (1, 0, 1) model, while others use the Additive and Multiplicative WINTER method. The daily stock price predictions of the five issuers from April 14, 2021 to July 15, 2021 tend to increase. This is presumably because investors tend to increase their capital due to the effect of health protocols that are getting tighter during the second wave and the assumption is that when the level of virus spread has begun to decline, the health sector shares will continue to rise, although not significantly.